Manfaat Rebusan Daun Seledri Apium Graveolens L Sebagai Obat Pada Pasien Hipertensi - muhammad ilham rivany (Yayasan Pendidikan Medika Indonesia, 2021)
Hypertension is one of the leading causes of premature death in the world and there have been 10.4 million deaths caused by hypertension. An estimated 1.13 billion people worldwide suffer from hypertension and most are from developing countries. Pharmacologically, chemical drugs are widely used to overcome hypertension, besides that currently many researchers are beginning to research plants that can be used as therapy one of them to overcome hypertension. One of the non pharmacological therapies to lower blood pressure is complementary therapies, where one of them is the use of celery herbs. Celery (Apium graveolens) is proven to successfully lower high blood pressure because it contains potassium that is diuretic which is needed to help the body release water and sodium in order to lower blood pressure. The method used is a review literature method of 12 articles taken from google scholar and PubMed, published in 2014 to 2018. From some research conducted obtained the results that celery plants are useful as a hypertension drug. Apigenin compounds are vasodilators so as to lower blood pressure.